International peacekeeping
International Peacekeeping examines the theory and practice of peacekeeping and peace operations as instruments of policy at an international level. From a broader perspective the journal also reflects debates about peacebuilding and monitoring of agreements, preventive deployments, sanctions, international policing, protection of aid in internal disputes, and the relationship between peacekeepers, state authorities, rival factions, civilians and non-governmental organizations. The journal promotes debate on these issues in the fields of international politics, military studies, international law and development studies.